Winter Species Promote Phytoremediation of Soil Contaminated with Protox-Inhibiting Herbicides - ALVES,C. (2019)
ABSTRACT: Phytoremediation comprises one of the main forms of decontamination of organic and inorganic substances in the soil, being economically viable and with a low environmental impact. The aim of this study was to verify the efficiency of winter plant species in the phytoremediation of soil contaminated with fomesafen and sulfentrazone using cucumber as an indicator species to the presence of residue. The experimental design was a completely randomized design arranged in a 6 x 4 factorial scheme with four replications for each herbicide. Factor A consisted of the phytoremediator species black oats, garden vetch, radish, bird’s-foot trefoil, white lupine, and a treatment without prior cultivation. Factor B, on the other hand, consisted of the doses of fomesafen (0.000, 0.125, 0.250, and 0.500 kg h-1) or sulfentrazone (0.000, 0.300, 0.600 and 1,200 kg ha-1) applied in crop pre-emergence. At 45 days after sowing, the phytoremediator species were cut close to the soil. Subsequently, the bioindicator species of herbicide residues in the soil (cucumber) was sown in the pot. Phytotoxicity of herbicides to cucumber plants was assessed at 7, 14, 21, and 28 days after emergence (DAE). At 28 DAE, leaf area, height, and dry matter were determined in the bioindicator plant. Fomesafen and sulfentrazone doses interfered negatively with the assessed variables of cucumber when cultivated in succession to phytoremediator species. Cucumber phytotoxicity increased for all potential phytoremediator species as fomesafen and sulfentrazone doses increased. Sulfentrazone residues promoted the highest toxic effects on the bioindicator plant when compared to fomesafen. In general, black oats, radish, and white lupine were the species with the highest capacity to phytoremediate soil contaminated with fomesafen and sulfentrazone when applying the dose and twice the recommended doses of the herbicides.